PENGEMBANGAN MEDIA PERMAINAN KARTU UNHISTOR (UNO HISTORY) UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH PESERTA DIDIK KELAS XI SMA AS-SHOFA PEKANBARU - Wahyuni, Nuriyah; Ishak, Isjoni; Yuliantoro, Yuliantoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of technology and the increasing complexity of 21st-century educational challenges require adjustments in various aspects of learning, including history education. The problems occurring in history learning have resulted in low student achievement in comprehensively understanding historical material. This study aims to (1) develop the Unhistor (UNO History) card game media for the topic of the Indonesian National Movement; (2) determine the feasibility of the media; and (3) examine its effectiveness in improving the history learning outcomes of eleventh-grade students at SMA Islam As-Shofa Pekanbaru. This research employed a Research and Development (R&D) method using the 4-D model (Define, Design, Develop, Disseminate). Data collection techniques included observation, interviews, questionnaires, expert validation, as well as pretest and posttest assessments. Data were analyzed descriptively and quantitatively using feasibility percentages and N-Gain calculations. The results indicate that the Unhistor card game media falls into the “Very Feasible” category. Validation by material experts reached 88%, while media experts gave 94%. Student responses in the small-group trial reached 87.4%, and in the large-group trial 92.1%, both categorized as “Very Feasible.” In terms of effectiveness, in the small-group trial the average pretest score of 47 increased to 82.66 with an N-Gain of 0.67 (moderate category), while in the large-group trial the average pretest score of 48.2 increased to 85.1 with an N-Gain of 0.71 (high category). Therefore, the Unhistor card game media has proven to be highly feasible and effective in improving learning outcomes, motivation, and student engagement in history learning.